SARS-CoV-2, "common cold" coronaviruses' cross-reactivity and "herd immunity": The razor of Ockham (1285-1347)? - Nicola Petrosillo (MDPI AG, 2020)
After the rapid spread of coronavirus-19 infectious disease (COVID-19) worldwide between February and April 2020, with a total of 5,267,419 confirmed cases and 341,155 deaths as of May 25, 2020, in the last weeks we are observing a decrease in new infections in European countries, and the confirmed cases are not as severe as in the past, so much so that the number of patients transferred to intensive care for the worsening of the systemic and pulmonary disease is dramatically decreasing [...]